Pengaruh Pelatihan Digital Marketing terhadap Peningkatan Kinerja Pemasaran UMKM di Kota Yogyakarta - Chriswardana Bayu Dewa; Lina Ayu Safitri; Diah Pradiatiningtyas (Excellent, 2025)
Yogyakarta, one of Indonesia’s leading creative MSME centers, still faces challenges in implementing effective digital marketing strategies. This study aims to explicity analyze how digital marketing influences MSME marketing performance and to identify the key factors that strengthen or hinder its effectiveness. Using a qualitative descriptive approach with in-depth interviews, observations, and document analysis involving twelve MSME owners, the study found that training significantly enhances entrepreneurs’ skills in content creation, social media use, and online customer engagement. The study concludes that training positively impacts marketing performance reflected in increased online visibility, higher engagement, and sales growth but the sustainability of these improvements depends on digital literacy levels, mentoring availability, and access to digital infrastructure. MSMEs involved in digital business communities demonstrate more consistent long-term outcomes. Therefore, continuous support and contextualized training are essential to maximizing the long-term impact of digital marketing on MSME performance.